Digital Literature Understanding of Early Childhood Education Teachers in Pontianak, West Kalimantan - Lukmanulhakim; Andini Linarsih; Ady Setiawan (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The purpose of this research was to obtain information about Understanding Digital Literature Early Childhood Education (PAUD) Teachers in Pontianak in the class base, school culture base, and community base they have. This research approach is descriptive qualitative. Sources of data are PAUD teachers in Pontianak spread over 6 sub-districts with 30 institutions, and 90 teachers. Data collection with observation, interviews, and documentation studies. Data collection tools in the form of observation guides, interviews, and documentation. Data analysis by collecting, reducing, presenting, and drawing conclusions. The results concluded that the digital literacy of PAUD teachers in Pontianak in general was still lacking. This is due to: 1) class base: The number of digital literacy trainings attended by teachers is still very low, the intensity of the application of digital literacy in learning activities is still lacking and driven by Covid-19, the level of understanding of teachers is still low; 2) the basis of school culture: the number and variety of reading materials and digital-based teaching aids is still lacking, the frequency of use of digital learning resources is still lacking, the number of presentations of school information using digital media is less, policies regarding digital literacy is not optimal; 3) basic community: community support in the form of providing digital literacy facilities and infrastructure in schools. The level of involvement of parents, the community, and schools in the development of digital literacy is sufficient through the school's social community.